Effect of fiber treatment on physical and mechanical properties of natural fiber-reinforced composites: A review - Hosseini, Seyyed Behnam; Gaff, Milan; Li, Haitao; Hui, David (De Gruyter Open Ltd., 2023)
Due to environmental and financial concerns, there is a growing demand for composite materials in a wide range of industries, including construction and automotive industries. In 2020, the market for wood plastic composites was estimated to be worth $5.4 billion. By 2030, it is expected to have grown to $12.6 billion, with a compound annual growth rate of 8.9% between 2021 and 2030. The fundamental disadvantage of reinforced composites by natural fibers is the different nature of the hydrophilic lignocellulosic and the hydrophobic thermoplastic polymers, although natural fibers would lower total costs. These composites typically fail mechanically as a result of fiber debonding, breaking, and pull-out. In a fiber-reinforced composite, the matrix's function could be described as distributing the force to the added fibers using interfacial shear stresses. A strong connection between the polymeric matrix and the fibers is necessary for this procedure. Weak adhesion at the interface prevents the composite from being used to its maximum potential and leaves it open to attacks from the environment that could damage it and shorten its lifespan. Poor mechanical performance is caused by insufficient adhesion between hydrophobic polymers and hydrophilic fibers in natural fiber-reinforced polymer composites. Consequently, during the past 20 years, a variety of chemical, thermal, and physical methods have been employed to address these issues. These methods largely concentrated on the grafting of chemical groups that could enhance the interfacial contacts between the matrix and natural fibers. This review article aimed to give information on several types of fiber treatments and natural fiber-treated composites with a specific focus on their physical and mechanical properties.
Keywords: composite; mechanical properties; natural fiber; physical properties; polymer; treatment